Importance of Porch in Mediterranean Architecture - Salihoğlu, Turgay (European Journal of Sustainable Development, 2019)
With the Industrial Revolution, human beings have faced ecological problems. For this reason, the term ”Sustainable Architecture’’ came up in the architectural field. In 1987 the United Nations Environmental Commission redefined this term. Also in 1992, the United Nations Conference on Environment and Development in Rio de Janeiro, Brazil the human being adopted some principles. When we look at the principles of ”Sustainable Architecture“, we can briefly refer to these principles as ''Natural Climatization'' or ”Thermal Comfort“. In spite of all this process, many architects still produce projects under the name of a ''Modern Architecture'' without considering the culture of life formed by climatic conditions in this process. Because of this, most of the users lost their confidence in ''Modern Architecture''. This is not ”Sustainable Architecture’’. However, the housing built in the past in the rural areas and urban, and even the official buildings are an open laboratory. When the laboratory in Cyprus is examined we can say that, ''the Porch Planned'' type houses, which is developed by the experiments in the Rural Area Housings during the period, started to build also in the cities. We see this development, arising from the climatic conditions, in the Government Agency buildings and Bureaucrats and Military Officers' houses that has built by the British Rule which commands the Cyprus Island during 1878-1960. In addition, porch-planned houses are also seen in the houses that C.M.C (Cyprus Mines Coorparation), which started its activities in 1914 due to the rich copper deposits in the Lefke region, built for its employees. Keywords: Environment. Solar Radiations. Sustainable Architecture. Thermal Comfort. Porch.